Empowering Adolescents through School-Based Health Socialization: Menstruation and Puberty - Aryani, Neng Gina; Sirulhaq, Sekarmaji; Ratnasari, Ayu Bilqis; Ruhama, Alma Siti; Maulana, Yusup (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This community service activity focuses on the issue of low reproductive health literacy among students at SDN 1 Cikembar, Cikembar Subdistrict, Sukabumi Regency, particularly regarding menstruation, puberty, and Islamic values. Many students in grades 5 and 6, totaling 80 individuals, are influenced by myths and lack accurate information, leading to embarrassment and confusion in addressing physical changes. The objective of this service is to enhance students’ understanding of reproductive health, reduce stigma, and strengthen Islamic values in navigating puberty. The approach employed is a community-based outreach method with interactive strategies, including visual presentations, small group discussions, and Q&A sessions, conducted in a one-hour session. Students of Islamic Education (PAI) served as facilitators, integrating scientific explanations with Islamic values of purity (thaharah) and religious responsibility. Initial data were collected through observations and interviews to tailor the material to students’ needs. The results show significant improvements, with 85% of students understanding the menstrual cycle and hygiene practices, 80% comprehending religious obligations post-puberty, and 90% of female students feeling more comfortable discussing menstruation. Male students also demonstrated increased empathy (75%) toward their female peers’ changes. The activity successfully created a supportive discussion environment and reduced stigma, although time constraints posed a challenge. This service provides a tangible contribution to student empowerment and serves as a model for similar programs in other schools.